EDUCATIONAL EXPLOITING THE INFORMATION RESOURCES AND INVADING THE SECURITY MECHANISMS OF THE OPERATING SYSTEM WINDOWS 7 WITH THE EXPLOIT ETERNALBLUE AND BACKDOOR DOUBLEPULSAR: EDUCATIONAL EXPLOITING THE INFORMATION RESOURCES AND INVADING THE SECURITY MECHANISMS OF THE OPERATING SYSTEM WINDOWS 7 WITH THE EXPLOIT ETERNALBLUE AND BACKDOOR DOUBLEPULSAR - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper an educational exploitation of information resources and invading the security mechanisms of the operating system Microsoft Windows 7 with the exploit EternalBlue and backdoor DoublePulsar is conducted.